Buoyancy-driven flow for surface reaction on vertical walls in multilayered open cavities - Nepal Chandra Roy (Heliyon)
This study analyzes the influences of surface reactions on the natural convective flow, temperature, and oxygen concentration distributions in vertically placed multilayered cavities. A mathematical model for this problem is formulated with proper boundary conditions. At first, the governing equations are made dimensionless using the variable transformations. Then, those are solved utilizing the finite element method (FEM), and the stream function is calculated from the Poisson equation. Numerical results show that the maximum stream function is significantly increased while maximum temperature and remaining oxygen concentration are considerably decreased with higher Rayleigh number. On the contrary, the buoyancy force parameter and the Lewis number cause an increase in maximum values of stream function and temperature but a decrease in remaining concentration. For increasing Lewis number and reactant consumption parameter, the flow structure in cavities significantly changes. In addition, maximum values of stream function and temperature are significantly increased with the increase of the heat release parameter. When the opening heights are wider, maximum stream function and remaining concentration are higher, however maximum temperature first becomes lower and then becomes higher. For any value of the parameters, the maximum flow intensity occurs adjacent to the bottom opening of the top cavity of the multilayered open cavities. However, maximum temperature is seen at the top left corner of the top cavity of the system.